The Influence of Emotional Intelligence on the Academic Achievement of Class IX Male Students at MTs Ummul Quro Al-Islami Bogor - Pirman; Nur Ramadhan (al-Afkar, Journal For Islamic Studies, 2024)
Intelligence and emotions play an important role in the learning process for students. Without participating in the emotional appreciation of the topics discussed in class, IQ cannot function properly. However, IQ and EQ are usually the key to a student's success in school. Researchers want to conduct additional research on "The Influence of Emotional Intelligence on Student Academic Achievement" by looking at the context of the problems described above. Descriptive correlational research is used in this research, which takes a quantitative approach and reveals the influence between variables in numbers. The variable in question is the influence of emotional intelligence (X) on academic achievement (Y). The population of this study was 392 students, and a sample of 80 students was taken. Emotional intelligence of class IX male students at MTs Ummul Quro Al-Islami, based on questionnaires distributed to 80 male students, the dominant score obtained was 31% in the sufficient category, so it can be concluded that the level of emotional intelligence of class IX male students at MTs Ummul Quro Al-Islami Islamic is categorized as sufficient. The academic achievement of class IX students at MTs Ummul Quro Al-Islami, based on the average report card score of 80 male class IX students, is cognitively 48%, affectively 25%, psychomotorically 54%. The regression test shows a correlation of 0.009 which is smaller than 0.1, which indicates that variable X has an effect on variable Y, based on research findings. Emotional intelligence influences academic achievement among students.